Industri Farmasi dalam Kajian Produk Halal: Pendekatan Systematic Literature Review - Hakim, Ummu Habibah; Anggraeni, Fani (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2023)
The halal industry is not only focused on the halal food sector, but has also developed into other sectors, including the pharmaceutical industry. This is supported by an increasing in the market share of halal medicines and the high interest of the Muslim community in using halal medicines. However, this increase in public interest and demand is not comparable to the availability of halal pharmaceuticals in Indonesia. This article will analyze how halal standardization is applied to products in the pharmaceutical industry. This study was designed using the Systematic Literature Review (SLR) method for browsing previous research that published within the 2013-2023 timeframe. The results showed that a product can be considered halal if it can be proven to be free from the critical point of drug halalness and meets the requirements in the halal assurance system (HAS) 23000. Among the obstacles in its implementation are a lot of use of imported raw materials that are not guaranteed to be halal, the complexity of the halal certification process in the pharmaceutical industry and the human resource factor.